Potensi Limbah Gulma Alang-alang dan Saliara sebagai Bioherbisida untuk Pengendalian Gulma secara Pra Tumbuh - Sari, Vira Irma; Napitupulu, Beatrix Sofranes; Christy, Julieta; Nafisah, Rouzatul (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2025)
Alang-alang (Imperata cylindrica) and Saliara (Lantana camara) are dominant weeds in several crop cultivation areas, so that when control is carried out, waste from both weeds will be produced in large quantities. Management of waste from both weeds can be done by utilizing it as a more environmentally friendly bioherbicide. Bioherbicide application is carried out pre-growth so that control is carried out faster and attacks newly germinated weed seeds, so that weeds do not appear on the surface and weed control activities will be more efficient. Alang-alang is the most dangerous weed and is highly avoided because it contains allelochemical compounds that can inhibit the growth of the main plant, this compound is found in all parts of the weed but is found most in the roots. Saliara also has a high content of allelochemical compounds which causes a distinctive aroma from its leaves. The allelochemical content of both weeds can be used as active ingredients in bioherbicides and is effective in controlling other weed species. Several studies have reported that bioherbicide extracts from both weeds are effective in inhibiting weed growth so that they can be used as an alternative to herbicides. However, bioherbicide application must be carried out with the right technique and concentration so as not to interfere with and inhibit the growth of the main plant.